Funds available for research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Directorate General for Science, Research and Development of the Commission of the European Communities (CEC) has announced a second research and development programme 'Science and Technology for Development'. This consists of two...